Down‐regulation of miRNA‐27b‐3p suppresses keratinocytes apoptosis in oral lichen planus. Issue 6 (11th April 2019) - Chen, Junjun; Wang, Yufeng; Du, Guanhuan; Zhang, Wenyi; Cao, Tianyi; Shi, Linjun; Wang, Yanni; Mi, Jun; Tang, Guoyao
Abstract: Oral lichen planus (OLP) is considered a precancerous lesion with no known cure. Recent studies reported that abnormal regulation of apoptosis was involved in the pathogenesis of OLP. Next generation sequencing was used to screen the candidate microRNAs and genes in biopsies from patients with OLP and healthy mucosa. Human oral keratinocytes were transfected into the related oligonucleotides of miR‐27b‐3p/cyclophilin D and their control groups. Apoptosis was detected by TdT‐mediated dUTP nick end labelling and flow cytometry. The levels of mRNA and protein were detected by quantitative PCR, Western blots, and enzyme‐linked immunosorbent assays, respectively. Luciferase assays were performed to detect the luciferase activities of miR‐27b‐3p and cyclophilin D. Here, we showed that basal epithelium apoptosis was reduced and the miR‐27b‐3p levels were decreased in clinical OLP samples. We also found that down‐regulation of miR‐27b‐3p inhibited epithelial keratinocyte apoptosis by up‐regulating cyclophilin D expression. Moreover, cyclophilin D increased the protein stability of Bcl2 through direct binding, and Bcl2 suppressed caspase9/3 activation and cytochrome C release. Taken together, these data showed that miR‐27b‐3p regulated keratinocyte apoptosis through cyclophilin D/Bcl2 signalling, suggesting the miR‐27b‐3p regulated the pathogenesis of OLP.